THE ABORTION DEBATE: AN AFRICANIST ETHICAL APPROACH - Wesley Taiwo Osemwegie (Universitas PGRI Madiun, 2022)
: The prevalence of abortion is of central concern to all societies in the world including traditional African societies. It is perturbing that, virtually in all countries; the phenomenon overtly presents itself and the need to legalize it or not continues to elicit responses and very strong arguments in defence or against. Given this, my aim in the work is to meticulously explicate the abortion controversy and evaluate the reasonability or illogicality from the parameters of the African value system. My discovery reveals that there seems to be no place for abortion in the traditional African societies as clearly manifested by the ethos of ‘dos and don’ts’ and values that characterized African ontological environment and world-view. As a method, I approached and analyzed the abortion controversy by subjecting them to the Bini ethical standard. Furthermore, the work examines the nature of abortion and the real dangers that come with it. I argued that procuring abortion for whatsoever reason(s), as may be upheld by the consequentialist ethicists and some feminist thinkers is inadmissible and morally prohibited. I concluded that the argument― that mothers have right over their body, perhaps a way of justifying abortion, is simply a relative position and an outright manifestation of some western radical propaganda for global feminism.